Main Results of International Cooperative research in the Study of Plant diversity in Vietnam, 1993-2002 - Regalado Jr., Jacinto; Harder, Daniel K.; Hiep, Nguyen Tien; Huong, Nguyen Thi Thanh; Averyanov, Leonid V.; Loc, Phan Ke (VNU Journal of Science: Natural Sciences and Technology, 2003)
Abstract